Clinical Pathway Implementation with the Quality of Service and Satisfaction Patient of DM Gangrene in the General Surgery Poly at RSUD Ra Basoeni Gedeg Mojokerto - Evy Maretnawati; Sandu Siyoto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
DM management requires collaborative and integrated team involvement in working with patients to set goals and implement treatment for patients. The need for treatment to individuals with DM helps provide psychological support, psychomotor skills, promote self-management, and set goals for better and optimal outcomes. Therefore, in the care of DM patients, it is necessary to apply services that can help patients in undergoing treatment better, one of which is by applying clinical pathways. The design of this research is crossectional analytics. The variables of this study are the application of clinical pathways as independent variables as well as quality of service and patient satisfaction as dependent variables. The population of all dm gangrene patients in the General Surgery Department of RSUD RA Basoeni Gedeg Mojokerto was 137 patients in February - March 2020. Samples were taken with simple random sampling techniques as many as 105 respondents. The data was collected by questionnaire and processed using editing, coding, scoring and tabulating and tested with chi square test. The results of this study showed that partially and simultaneously independent variables influence the occurrence of dependent variables due to the value of < of 0.05. The application of clinical pathways can help patients know all forms of services that will be received from the beginning of the action until the patient returns home. Mechanism of application of clinical pathway will be a basis of communication that is built with good quality between hospital staff and patients so that patients will receive the maximum service and patients are satisfied with the service